Multiple Regression Model on Selling Price, Sales Volume, Raw Material Costs, and Direct Labor Costs on Profit - Machfiroh, Ines Saraswati; Maulida, Afna (Universitas Bumigora, 2025)
During its operations, a company always aims to achieve increased profits. The case of PT Ciomas Adisatwa RPA Unit Banjarmasin from 2019 to 2022 demonstrates a trend of rising profits. Several factors can influence a business's profitability, including selling price, sales volume, and incurred costs. The objective of this study is to analyze how the profit of PT Ciomas Adisatwa RPA Unit Banjarmasin is influenced by selling price, sales volume, raw material costs, and direct labor costs. This research applies a quantitative descriptive approach using secondary data. The monthly data utilized spans from 2019 to 2022, comprising a total of 48 data points. The results of the study show that selling price, sales volume, and raw material costs have a significant effect on the profit of PT Ciomas Adisatwa RPA Unit Banjarmasin, while direct labor costs do not have a significant influence. These findings imply that pricing strategies and increased sales volume are the main factors that can enhance the company's profitability. Additionally, controlling raw material costs is a crucial aspect that must be managed efficiently to avoid burdening the cost structure. On the other hand, direct labor costs can be minimized through production efficiency and the use of technology without compromising production output. Therefore, the company should focus on pricing strategies, marketing, and raw material cost efficiency as key measures to sustainably increase profits.